European Small Business Finance Outlook: December 2017 - Helmut Kraemer-Eis; Antonia Botsari; Salome Gvetadze; Frank Lang; Wouter Torfs (European Investment Fund (EIF), 2017)
This European Small Business Finance Outlook (ESBFO) provides an overview of the main markets relevant to EIF (equity, guarantees, securitisation, microfinance). It is an update of the June 2017 ESBFO edition. We start by discussing the general market environment, then look at the main aspects of equity finance and guarantees/SME Securitisation (SMESec). Finally, before we conclude, we briefly highlight important aspects of microfinance in Europe and – for the first time and due to the rising importance of the segment – we complement our analysis by a chapter on Fintech.
Keywords: 330